Transoral Open Reduction for Subcondylar Fractures of the Mandible Using an Angulated Screwdriver System. Issue 3 (September 2015) - Nam, Seung Min; Kim, Yong Bae; Cha, Han Gyu; Wee, Syeo Young; Choi, Chang Yong
Abstract : Background: The management of subcondylar mandibular fractures has been a matter of controversy. Although closed reduction is the most useful method, it can be difficult to achieve anatomical reduction with this technique compared with open reduction and internal fixation (ORIF). Most surgeons prefer to treat subcondylar fractures by extraoral approaches rather than intraoral approaches because extraoral approaches provide good visualization of the operative field. The retromandibular, submandibular, and perilobular approaches are commonly performed in the treatment of displaced condylar or subcondylar fractures and that the functional results of these treatments are good. However, extraoral approaches have a high rate of surgical complications such as salivary fistula formation, visible scarring, and facial nerve injury, compared with intraoral approaches. Therefore, this clinical study evaluated the clinical results of ORIF for mandibular subcondylar fractures through a transoral approach using an angulated screwdriver system without endoscopic assistance. Methods: A study was conducted between March 2011 and October 2012. Eleven patients with subcondylar fractures of the mandible were treated through a transoral approach using an angulated screwdriver. There were 10 male patients and 1 female patient aged 21 to 72 years (mean, 38 years). Nine patients had a symphyseal or parasymphyseal fracture, and 2 patients had isolated subcondylar fractures of the mandible. Results: Eleven patients with subcondylar fractures of the mandible were treated with a transoral approach using an angulated screwdriver. The subcondylar fracture was on the left side in 6 patients and on the right in 5. All patients achieved satisfactory ranges of temporomandibular joint movement with an interincisal distance of more than 40 mm without deviation and stable individual centric occlusion. The maximum operation duration was 165 minutes, and the average duration of ORIF was 97 minutes. The association between the operation duration and the number of operations was statistically significant. Conclusions: Our clinical study shows that subcondylar fractures of the mandible can be treated using an angulated screwdriver system through a transoral approach and that this technique provides reliable, satisfactory, and safe clinical outcomes.